Growth of hydroponic lettuce with optimized mineral and organomineral nutrient solutions - Antonio F. Monteiro Filho; Márcia R. Q. A. Azevedo; Carlos A. V. de Azevedo; Josely D. Fernandes; Carisa R. da Silva; Yuri dos S. Silva (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The objective of this study was to evaluate the growth of crisp lettuce in hydroponic cultivation, following the nutrient film technique (NFT), using optimized mineral and organomineral nutrient solutions. The experiment was set in 8 x 3 factorial scheme, with treatments distributed in randomized blocks and split plots, with three replicates. The plots corresponded to eight nutrient solutions, of which four were mineral solutions with chemical composition suggested by Bernardes, Furlani, Castellane & Araújo and Ueda, and four were organomineral solutions, suggested by this research with chemical composition similar to those of the previously mentioned mineral solutions. The subplots corresponded to three varieties of crisp lettuce: Thaís, Vanda and Verônica. At 25 days after transplanting, the following parameters were evaluated: stem and crown diameter, root length, leaf area and number of leaves. For stem and crown diameters and number of leaves, the mineral solutions promoted the highest means. The mineral solution of Furlani and the organomineral solutions, except the modified solution of Castellane & Araújo, promoted the greatest root lengths. The smallest leaf area was obtained in the organomineral solution of Ueda. The cultivar Verônica had the highest root length and stem diameter.